PENGARUH KEPEMIMPINAN, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA CV. ISTANA BOGA SEMARANG) - Marybeth Carollyna, 11.05.51.0016; Priyono, Bambang Suko (Students Journal of Economic and Management, 2016)
This study analyzed the Influence of Leadership, Compensation, and motivation on employee performance in CV. ISTANA BOGA Semarang. The research object in this paper is CV.ISTANA BOGA Semarang. The sampling technique in this research is to use the Simple Random Sampling totaled 135 respondents. Analysis of the data used include the product moment test validity, test reliability coefficient alpha (Alpha Cronbrach), multiple regression analysis, t test to test and prove the research hypothesis. The results of the research are: (1) Leadership positive and significant effect on the performance employee, the more often the motivation is given it will improve the performance of employees (2) Compensation not significant and positive effect on employee performance, the training level of discipline given employee will be increased. (3) Motivation positive and significant effect on employee performance, the better the work environment employees will feel comfortable. Â Keywords: Leadership, Compensation, Employee Motivation and Performance